ANDROID BASED MULTIMEDIA APPLICATION FOR RECOGNIZING LETTERS AND SENTENCES FOR DEAF - Fahrul, Fahrul; Nirsal, Nirsal (Informatika, Universitas Jenderal Soedirman, 2024)
This research aims to create an Android-based guide to reading letters and sentences for deaf children at UPT Special School (SLB) Negeri 1 Palopo. This research process aims to help deaf students read letters and sentences, so with this letter and sentence reading guide application, it can make it easier for deaf students to learn anywhere and anytime. The type of research used in this research is Research and Development (R&D), using the ADDIE model. This system design uses MIT App Inventor Software. This Android-based letter and sentence recognition application for deaf children has been tested by media experts using black box testing. The results of research validation from two validators obtained an average result of 3.85 with a very feasible category. The conclusion of this research shows that Android-based learning media has been proven to be very feasible. The results of the research were implemented in the form of an Android application as a learning medium for recognizing letters and sentences for deaf children as a teaching medium that can be used at UPT Special School (SLB) Negeri 1 Palopo.